Narciso sem espelho - Bicalho, Angélica Aparecida de Oliveira (2010)
One of the characteristics of contemporary society is the validation of the functions and attributes of image: looking, viewing and seeing can be considered as a hyper-cognization of vision. To move from the behavior of those who are able to see and those who are blind can mean much more than the contrasts between seeing and not seeing, between light and dark, or other antinomies. Anthropological studies based only on what is explicit, what is visible, and what can be observed are able to exacerbate differences and be represented as poor guides of what people do, know, or think. However, blind individuals have been the object of systematic studies, as carriers of special needs or in the condition of a minority to be included. Although the term carriers of special needs is a traditionally accepted way to refer to a social group, without the label of handicap , it is not self-clarifying, for, if considered individually, everyone presents specific, special needs. The eyes, blindness and vision were analyzed under the perspective of science and mythology. The aim of this work is to enter the sea of blindness without stereotypes, that is, to attempt to understand the invisible and lacunary universe of thought in which the blind person is located and the sensitive and relatively continuous world the visible world represented by the screen. For this work, we have analyzed two movies: Blindness and Red Like the Sky and the documentary Janela da alma [Window of the Soul]. University students from the São Gabriel campus, from PUC Minas, were census-like surveyed in order to identify those blind and carrier of low vision, who presented their perspective in relation to the seventh art